Prevalence and Outcomes of COVID-19 Infection and its Associated Socio-demographic Factors among Population in North-East Region of Bangladesh (Bangladesh Journal of Infectious Diseases, 2024)
Background: Different countries and different regions within those countries have exhibited distinct COVID-19 infection prevalence and clinical outcomes. These are important to assess owing to understanding the magnitude of the disease in a particular area and to initiate appropriate intervention.Objective: The objective of the present study was to investigate the prevalence and outcomes of COVID-19 infection, and its associated sociodemographic factors among the population at the Shylet district in Bangladesh.Methodology: This retrospective study was carried out in the Department of Microbiology at Sylhet MAG Osmani Medical College, Sylhet, Bangladesh from 4 April to 6 September 2020. Patient data collection was collected from different healthcare institutions located in Sylhet. Those patients attended the institutions to diagnose COVID-19 infection during the ongoing pandemic. Microsoft Excel and SPSS software was used for the data analysis. P< 0.05 at a 95.0% confidence interval was specified as the standard of significance.Results: Participants aged more than 60 years old showed the highest rate of death (8.3%) and the lowest proportion of cure (91.7%). A significant association has been found in the COVID-19 infection outcome of the participants with their age, occupation, and place of treatment for infected people (p